GAYA KEPEMIMPINAN TRANSAKSIONAL, GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI KERJA: MENINGKATKAN EFEKTIVITAS APARAT PEMERINTAH DI DESA TAKKALASI - Halmia; Ramadhan, Muh. Rohady; Dema, Herman (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
The purpose of the study is to determine the Influence of Transactional Leadership Style and Transformational Leadership Style on Work Motivation, and to find out the factors that affect the Work Motivation of Government Apparatus in Takkalasi Village, Maritengngae District, Sidenreng Rappang Regency. The approach of this research method uses a quantitative descriptive approach, the population and sample in this study are village officials as many as 12 people. The data collection techniques used in this study are observation, questionnaires, and literature studies. The collected data was then processed and analyzed using quantitative descriptive analysis techniques with the help of descriptive statistics using SPSS and percentages. The results of the study showed that the recapitulation of the Influence of Transactional Leadership Style in Takkalasi Village, Maritengngae District, Sidenreng Rappang Regency with a percentage result of 86% means that it is very influential in terms of employee rewards and exception management.